2009
DOI: 10.1075/sibil.41.09koo
|View full text |Cite
|
Sign up to set email alerts
|

6. Two speakers, one dialogue: An interactive alignment perspective on code-switching in bilingual speakers

Abstract: In code-switching research, a distinction can be made between approaches that focus on linguistic and cognitive variables within single individuals and approaches that emphasize processes between individuals and the social and interactive context. These approaches differ in terms of both theory and methodology, and are difficult to integrate. In this chapter, we build on recent theoretical developments in psycholinguistics and propose a model of interactive alignment in code-switching. The model takes dialogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 60 publications
2
15
0
1
Order By: Relevance
“…Fifth, as listening and speaking involve the same mental lexicon (e.g., Cutler, 2012;Levelt et al, 1999;Liberman, Cooper, Shankweiler & Studdert-Kennedy, 1967), hearing a cognate might affect the level of activation of language subsets in a similar way as producing one. Studies on SYNTACTIC priming show that perceived speech affects produced speech, both monolingually (Konopka & Meyer, 2014;Pickering & Ferreira, 2008) and crosslinguistically (Hartsuiker & Bernolet, 2017;Hartsuiker, Pickering & Veltkamp, 2004;Kootstra & Doedens, 2016;Kootstra, Van Hell & Dijkstra, 2009;Loebell & Bock, 2003). The tendency to codeswitch (Fricke & Kootstra, 2016) and the word order in codeswitched utterances (Kootstra, Van Hell & Dijkstra, 2010) are also subject to between-speaker priming.…”
Section: The Present Studymentioning
confidence: 99%
“…Fifth, as listening and speaking involve the same mental lexicon (e.g., Cutler, 2012;Levelt et al, 1999;Liberman, Cooper, Shankweiler & Studdert-Kennedy, 1967), hearing a cognate might affect the level of activation of language subsets in a similar way as producing one. Studies on SYNTACTIC priming show that perceived speech affects produced speech, both monolingually (Konopka & Meyer, 2014;Pickering & Ferreira, 2008) and crosslinguistically (Hartsuiker & Bernolet, 2017;Hartsuiker, Pickering & Veltkamp, 2004;Kootstra & Doedens, 2016;Kootstra, Van Hell & Dijkstra, 2009;Loebell & Bock, 2003). The tendency to codeswitch (Fricke & Kootstra, 2016) and the word order in codeswitched utterances (Kootstra, Van Hell & Dijkstra, 2010) are also subject to between-speaker priming.…”
Section: The Present Studymentioning
confidence: 99%
“…Research on bilingual language processing has shown that elements from bilinguals' two languages can be coactivated at all levels of processing and thus influence language production and comprehension (e.g., Kootstra, van Hell, & Dijkstra, 2009;Kroll, Bobb, & Wodniecka, 2006). Because code-switching involves the combined use of these co-activated languages in one sentence, it will probably be easiest to switch when the level of this co-activation is very high.…”
Section: A Processing-based Account Of Syntactic Choice In Codeswitchingmentioning
confidence: 99%
“…At the same time, by leaving participants free to generate the structure and positioning of their switches themselves, we stayed relatively close to corpus-based studies of code-switching. This embedding of relatively free code-switching in an experimentally controlled setting is a way to bridge the gap between linguistic and psycholinguistic approaches to the study of code-switching (see Gullberg et al, 2009;Kootstra et al, 2009, for further discussion).…”
Section: Word Order Effects On Code-switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…de Bot, Broersma, Kootstra et al 2009, for reviews). de Bot, Broersma, Kootstra et al 2009, for reviews).…”
Section: Lexical and Syntactic Factors In Cross-language Activation Aunclassified